Food system transition, territory and policies - Salavisa, I.; Ferreiro, Maria de Fátima; Bizarro, S. (12th CITTA International Conference on Planning Research, 2019)
The transition of food systems towards sustainability implies structural changes, namely the development of organic farming and alternative supply chains, where bottom-up experiments play a major role. In the case of food systems, the centrality of territorial units and scales is fundamental. Additionally, the multidimensionality of the innovation process with the inclusion of social, organizational and legal dimensions has to be considered. Bearing this in mind, the paper addresses the role of Metropolitan Areas in the food systems transition focusing on the case of Lisbon Metropolitan Area (LMA). This case is analysed according the following analytical dimensions: i) characterization of the Lisbon Metropolitan Area in socioeconomic and governance terms, namely land use patterns; ii) identification of the relevant policies involved, namely the Common Agricultural Policy; iii) presentation of bottom-up experiments located in LMA within the theoretical framework of the transition studies. The case studies were conducted on initiatives in the LMA food value chain (e.g. MARL, Quinta do Arneiro, Biofrade, Projecto Muita Fruta, Mercado Bio do Lumiar, Cantina de Escola Básica dos Olivais, etc.). In terms of results, the study identifies the main elements explaining the emergence and development of bottom-up experiments in LMA food system envisaging the transition towards sustainability, in a multidimensional perspective. The research has been developed within the project Spatial Planning for Change (SPLACH), through an interdisciplinary approach, resorting mostly to the transitions literature and economic geography.